Dissimilar Pronunciations of Same Letters or Groups of Same Letters Beginning with ‘E’ and ‘F’ Alphabets in Distinct Words of English Language - Koli, Dr. Uttam Balu (Journal of Research in Humanities, 2023)
This study brings in notice same letters or groups of same letters beginning with ‘E’ and ‘F’ alphabets having dissimilar pronunciations in distinct words of English language. Thirty same letters or groups of same letters beginning with ‘E’ and ‘F’ alphabets, i.e., e, ea, ee, eu, fa, fai, fe, fea, ffe, ffi, fi, fie, fla, flai, fli, flo, flou, flow, flu, flue, fo, foe, fra, fre, fri, frie, fro, fru, frui and fu, having dissimilar pronunciations in distinct words of English language have been described with one hundred and fifty-four appropriate examples including distinct words of English language and their exact phonetic transcriptions. These descriptions in the study will sufficiently enable readers to become master in the select part of learning. The introduction, hypothesis, objectives, research methodology, limitations, significance, findings and conclusion together with the attachment of the list of references have been given.